THE IMPACT OF QUARRYING ON THE ENVIRONMENT AND MITIGATION EFFORTS IN THE KENDENG MOUNTAINS OF SOUTH PATI - Ahmad Kasyfin Nur; Faizuna Tathmainnul Qulub; Dany Miftah M. Nur (International Journal of Multidisciplinary Reseach, 2025)
This study aims to analyze the environmental impacts of Class C mining activities and the mitigation efforts undertaken in the Kendeng Mountains region, South Pati, particularly in the villages of Sumbersari, Gadudero, and Wegil. The research employed a qualitative descriptive approach through field observations and interviews with local communities and village authorities. The results indicate that mining activities have led to land degradation, erosion, flooding, and a decline in groundwater quality. Beyond ecological impacts, social tensions have emerged due to conflicting economic interests among residents. Mitigation efforts such as land reclamation, water resource conservation, and the application of environmentally friendly mining technologies have been initiated but remain suboptimal. Strengthened supervision, law enforcement, and active community participation are essential to achieving sustainable mining management. This study highlights the importance of consistently implementing environmental policies to balance development needs with environmental conservation.